1979
DOI: 10.2307/1936866
|View full text |Cite
|
Sign up to set email alerts
|

Competition, Foraging Energetics, and the Cost of Sociality in Three Species of Bees

Abstract: Competition among three species of bees (Apis mellifera, Bombus sonorus, and Xylocopa arizonensis) visiting Agave schottii was studied. Honeybees were found to predominate in the most productive habitats, Xylocopa in the least; Bombus as most abundant in patches of intermediate quality. It is suggested that these observations are consistent with a simple graphical model relating the standing crop of available nectar to foraging energetics and the additional costs of colonial life (cost of sociality). Temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
2
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 33 publications
9
71
2
1
Order By: Relevance
“…We recorded several wild bee species of the genera Andrena, Hylaeus, Halictus, Lasioglossum, and Osmia, which include a number of species considered as polylectic (Westrich, 1996). In general, polylectic bees might be more affected by competition with honey bees due to similar foraging preferences (Schaffer et al, 1979(Schaffer et al, , 1983Roubik, 1978;1980). Still, we found no clear evidence of competition between wild bees and honey bees regarding their foraging behaviour on Cistus flowers.…”
Section: Discussioncontrasting
confidence: 57%
“…We recorded several wild bee species of the genera Andrena, Hylaeus, Halictus, Lasioglossum, and Osmia, which include a number of species considered as polylectic (Westrich, 1996). In general, polylectic bees might be more affected by competition with honey bees due to similar foraging preferences (Schaffer et al, 1979(Schaffer et al, , 1983Roubik, 1978;1980). Still, we found no clear evidence of competition between wild bees and honey bees regarding their foraging behaviour on Cistus flowers.…”
Section: Discussioncontrasting
confidence: 57%
“…Interspecific competition is assumed to be a major factor in structuring foraging communities on flowers (Schaffer et al, 1979;Pleasants, 1981;Zimmermann and Pleasants, 1982;Schoener, 1987;Westrich, 1989;Corbet et al, 1995). However, the mechanisms underlying these interactions are difficult to test in the field.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that oligolectic species are more sensitive to competition than polylectic and social species (Westrich, 1989;Evertz, 1995). In contrast, Schaffer et al (1979) and Thorp (1996) assumed that high honeybee densities most detrimentally affect social generalists with a foraging behaviour similar to that of honeybees. The latter argument would apply to species such as Bombus terrestris, which is able to fly several kilometres and exploit bonanzas of one flower species on arable fields or mass resources in grassland (Hedtke, 1996;Osborne et al, 1999;Walther-Hellwig and Frankl, 2000;Goulson and Stout, 2001;Kreyer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A similar case of species coexistence was indicated by Davidson (1977) who studied desert seed-eating ant communities containing group and individually foraging species. Schaffer et al (1979), who analyzed the exploitative competition among three bee species visiting Agave flowers, demonstrated further evidence in which coexistence of similar species is maintained by the density specialization. In the present study, wasp species with narrow and wide diet breadth correspond to the high-and low-density specialist, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…Miller, 1967;Johnson and Hubbell, 1974), and 3. Species compete exploitatively for the same resource (e.g., Davidson, 1977;Schaffer et al, 1979). Here, four species of eumenid wasps coexisted in part by means of resource partitioning according to the prey size (1) and partly by means of differential diet breadths resulted by respective foraging strategies.…”
Section: Introductionmentioning
confidence: 99%